AN INTER-STATE MARITIME TERRITORIAL CONFLICT: A STUDY ON MALAYSIA’S CONFLICT RESOLUTION THROUGH PEACEFUL MEANS - Mohammad Zaki Ahmad; Musafir Kelana (Universitas Padjadjaran, 2005)
Inter-state maritime territorial disputes have always long been amongst contentious issues among the littoral states in the ASEAN region. Failure to judicially manage such disputes may lead to uncertainty-creating the possibilities of escalating into open inter-state war. Without border settlement, claimant states have to spend substantially for military and security resources to protect their interests in the contested maritime areas, rather than developing the economic resources of the areas. Any armed conflict not only costs human life but also adversely affects maritime enforcement cooperation and diplomatic relations of the claimant states, and the overall economic growth in the region. Thus, Malaysia taking into account on the adverse impact of unresolved maritime disputes, has successfully and peacefully resolved several of its maritime territorial disputes with its neighboring States, albeit some of the ongoing unresolved territorial disputes (e.g. Pedra Branca island and Spratly islands). These resolutions are achieved either through diplomatic channel or by mutual agreement with other claimant State to refer the dispute to the International Court of Justice for adjudication. Therefore, the paper’s general purpose is to review Malaysia’s conflict resolution through its peaceful approach in resolving the country’s various inter-state maritime territorial disputes. Specifically, the paper will analyze the diplomatic, legal and other peaceful approaches utilized by the Malaysian government to resolve these disputes, particularly involving its neighboring states, Singapore, Indonesia and Thailand. Keywords: maritime territorial dispute, Malaysia’s conflict resolution, conflict management, joint development, diplomatic negotiation and adjudication.